Biotin Interference in Clinical Immunoassays: A Cause for Concern - Holmes, Earle W.; Samarasinghe, Shanika; Emanuele, Mary Ann; Meah, Farah (Archives of pathology & laboratory medicine (1976), 2017)
To the Editor.-An increase in the use of biotin supplements by the general public is producing an increase in the number of reports of analytic interference in biotin-based immunoassays (BBAs) used to evaluate endocrine function.1,2 The fact that BBAs of similar design are currently used to diagnose and manage a wide range of other medical conditions, including anemias, malignancies, autoimmune and infectious diseases, and cardiac damage, raises the concern that the accuracy of results for other routine tests are compromised as well.3 Methods that use immunometric ("sandwich") or competitive formats are at the greatest risk for producing falsely decreased or falsely increased results, respectively, when biotin is present in the sample. Eighty-two of these were immunometric or competitive methods that had manufacturer-reported interference thresholds (IFTs) (ie, the concentrations above which exogenous biotin in the sample caused a difference of greater than ±10% in the test result) of less than 51 ng/mL. In this case, the risk of an erroneous test result could persist for up to 8 elimination half-lives (>6 days) for a method with an IFT of 2.4 ng/mL. [...]it might be necessary to avoid the use of some BBAs altogether when testing subjects who are using the 100-mg biotin supplements that are now available overthe-counter.2,5 The confluence of increased biotin supplement use by patients and the design limitations of many of the BBAs have already led to the misdiagnosis and mismanagement of patients.1-3 We are convinced that the risk of analytic interference by biotin supplements is a serious problem that needs to be more widely recognized and promptly addressed by health care providers, directors of clinical laboratories, and decision makers in the clinical diagnostics industry.